PEMBENTUKAN KELOMPOK TARUNA WISATA DI GAMPONG LHOK JOK KECAMATAN KUTA MAKMUR, ACEH UTARA - M. Nazaruddin; Rizki Yunanda; Richa Meliza; Ade Ikhsan Kamil; Awaluddin Arifin; Nulwita Maliati (Universitas Malikussaleh, 2023)
Lhok Jok Village, Kuta Makmur District, North Aceh Regency has a beautiful river flow and the fruits are many and varied in every season. Some villagers said that the tourism potential in Lhok Jok Village can bring prosperity and has the potential to be built even greater than today. Income is an important goal for the sustainability of the tourist area. Especially with the current conditions where the impact of the stipulation of Covid-19 as a pandemic has caused changes in all lines of human life around the world, including Lhok Jok itself as one of the gampongs that has a tourist destinations with natural potential. Tourist locations in Lhok Jok also have another problem, that is not all components of the village community in Lhok Jok are aware of the benefits of the tourist destination itself. This unconsciousness comes from the lack of participation of the community in managing tourist destinations. In addition, the involvement of other very important components is also an obstacle to the management of Lhok Jok Village as a tourist destination with potential for natural beauty. For this reason, the role of youth in tourist destinations is very important and significant in the development of the Tourism Village in Lhok. Because youths are an educated group who have greater access to information technology in terms of introduction and sharing of information on tourist destinations.